Comparison of birth weight prediction equation and tactile assessment for estimation of fetal weight in uncomplicated term singleton pregnancies - Gupta, Himanshi; Chopra, Kanika; Agrawal , Swati; Yadav, Reena (Bangladesh Journal of Medical Science, 2025)
Background Estimation of fetal weight is of utmost importance in birth planning. Various methods such as ultrasonography and clinical methods such as tactile assessment by Leopold’s manoeuvres or by equation-based methods are in vogue for the estimation of fetal weight. However, available literature is inconsistent on the best method. The aim of the present study was to compare the accuracy of estimating fetal weight by Leopold’s manoeuvre and Johnson’s formula, in singleton term pregnancies. Methods This was a prospective observational study conducted in the Department of Obstetrics and Gynaecology of a tertiary care hospital in Delhi over a period of 3 months following institutional ethical committee clearance. A total of consecutive 100 pregnant women admitted for delivery in the obstetric unit were included in the study following inclusion and exclusion criteria. The outcome was to compare absolute error in weight (in grams), absolute percentage error and percentage of estimates within 10% for fetal weight estimation using Leopold’s manoeuvre and Johnson’s formula versus actual birth weight taken as gold standard. Results The mean estimated fetal weight by Johnson’s formula was 4.00 ± 0.59 kg (range 2.64-5.74 kg) and by Leopold’s manoeuvre was 2.88 ± 0.30 kg (range of 2.30-3.80 kg). The mean actual baby weight was 2.84 ± 0.42 kg (range 2.00- 3.89 kg). The difference from actual baby weight was found to be significantly more by Johnson’s formula as compared to Leopold’s method. Conclusion Tactile assessment by Leopalds manuover is better than equation-based methods for estimating fetal weight. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 641-646